Legal Aid and Community Empowerment in Trademark Protection for Public Procurement: Comparative Reflections from Indonesia, the United States, and Spain - I Gede Agus Kurniawan; Khalid Mustafa; Putu Aras Samsithawrati; Fradhana Putra Disantara; Dinara F. Abdunayimova; Antonio Gutiérrez-Pozo (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
The increasing integration of intellectual property protection into public procurement has transformed trademarks from private commercial assets into strategic legal instruments that support fair competition, legal certainty, and accountable public governance. Nevertheless, many micro, small, and medium enterprises (MSMEs) continue to face significant barriers in obtaining trademark protection due to limited legal literacy, inadequate legal assistance, and fragmented institutional support. This study aims to examine the contribution of legal aid to strengthening trademark protection for business actors participating in public procurement, analyze how community empowerment is institutionalized in Indonesia, the United States, and Spain, and formulate a more inclusive legal framework for Indonesian public procurement through comparative legal analysis. This research employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials consist of legislation, international legal instruments, academic literature, government reports, and institutional publications, which are analyzed through descriptive, comparative, and prescriptive methods. The findings demonstrate that legal aid should be reconceptualized as a preventive governance instrument encompassing legal education, trademark registration assistance, institutional collaboration, and community empowerment rather than merely litigation services. Comparative analysis reveals that the United States and Spain have developed integrated institutional models involving government agencies, universities, legal clinics, professional organizations, and business communities, whereas Indonesia continues to experience fragmented institutional coordination and limited preventive legal support. Accordingly, Indonesia should reconstruct its trademark protection framework by institutionalizing collaborative legal assistance, strengthening trademark literacy, integrating intellectual property protection into public procurement policies, and enhancing interagency cooperation to promote legal certainty, fair competition, inclusive economic participation, and sustainable public procurement governance. This aligns with Sustainable Development Goals (SDGs) 9: Industry, Innovation, and Infrastructure.